Fundusze unijne jako szansa wzrostu konkurencyjności przedsiębiorstw agrobiznesowych - Sikorska, Daria; Wielewska, Izabela (EU Funds as a Chance of Increase in Competitiveness of Agricultural Companies, 2006)
EU funds are the most important part of structural policy. They may be allocated for the development of countryside infrastructure and for modernization of farms and agricultural companies.Agricultural companies use structural funds to adapt themselves to the EU standards. They modernize their production lines and the buildings in order to comply with EU veterinary requirements.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 307-311